Estrogens desensitize MCF-7 breast cancer cells to apelin-induced autophagy and enhanced growth under estrogen starvation: a possible implication in endocrine resistance: MCF-7 cells growth under estrogen starvation by apelin - Bouchelaghem, Rim; Mader , Sylvie; Gaboury, Louis; Messarah, Mahfoud; Boumendjel, Mahieddine; Boumendjel, Amel (Cellular and Molecular Biology, 2022)
Apelin-13 is an adipokine known for its growth-inducing effects on human breast cancer cells in an estrogen-containing environment. However, the response of these cells to apelin-13 in the absence of estrogen and its association with the expression of the apelin receptor (APLNR) has not yet been investigated. In the present study, we show that the breast cancer cell line MCF-7 expresses the APLNR as shown by immunofluorescence and flow cytometry, under conditions of ER starvation and that culture of these cells in the presence of apelin-13 results in an increased growth rate and a diminished autophagy flux. Moreover, the binding of APLNR by apelin-13 resulted in an increased growth rate (assayed by AlamarBlue) and a diminished autophagy flux (monitored by Lysotracker Green). The latter observations were reversed in the presence of exogenous estrogen. Finally, apelin-13 induces the deactivation of the apoptotic kinase AMPK. Taken together, our results show that APLNR signaling in breast cancer cells is functional and prevents tumor growth under conditions of estrogen starvation. They furthermore suggest an alternative mechanism of estrogen-independent tumor growth thereby positioning the APLNR-AMPK axis as a novel pathway and a possible therapeutic target in endocrine resistance of breast cancer cells.